Relationship Between Evaluation and Motivation of the Learner - Krejčová, Markéta (Univerzita Pardubice, 2012)
The theoretical part of this diploma thesis presents the concept of evaluation, including the definition, types, forms, functions and tools of evaluation, which focus on testing and different types of tests. Further, the concept and evaluation of communicative competence are discussed. Hereafter, the definition of motivation is introduced, followed with the essential approaches that underlie motivation, types of motivation and basic tips how to evoke and maintain motivation among students. Finally, the theoretical part offers an opinion on the link that exists between evaluation and motivation, based on the theory of both concepts. The practical part contains a research which provides an insight into reality of evaluation and motivation, from the points of view of the students, teachers and the author of this diploma thesis. To the above mentioned purpose, observations, questionnaires with open question for the teachers and questionnaires with multiple choice for the students were chosen.
Vztah mezi hodnocením a motivací žáka
Keywords: hodnocení; typy; formy a funkce hodnocení; nástroje hodnocení; motivatice; různé přístupy k motivaci; typy motivace; vztah mezi hodnocením a motivací; evaluation; types; forms and functions of evaluation; tools of evaluation; motivation; various approaches to motivation; types of motivation; connection between evaluation and motivation